Stability and morphology-dependence of Sc3+ ions incorporation and substitution kinetics within ZnO host lattice - YUMAK YAHŞİ, AYŞE (ELSEVIER SCI LTD, 2015)
In this study, sol-gel spin coating route was carried out to prepare Scandium doped ZnO thin films with different controlled percentage (1-7%). Particularly, it has been demonstrated, through original conjoint morphological-structural and optical investigations, that some interesting physical properties were induced. Indeed, X-ray diffraction (XRD) analysis shows that (002) preferential crystalline plane for Sc doped ZnO films was kept along with ZnO hexagonal wurtzite structure, although Sc doping seemed to cause a decrease in crystallinity. Except for 1 at% Sc doping ratio, optical band gap changes reversely with Urbach energy with a decrease in optical gap and a broadening of the absorption tail. Ab-initio calculations of lattice dynamical properties outlined additional strong hybridization between Sc and O atoms and show the stability of Scandium doped ZnO. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Zinc oxide; Scandium; Optical properties; Single oscillator model; Urbach tailing; Dielectric constant; Amlouk-Boubaker opto-thermal; expansivity psi(AB); SI/AL HETEROJUNCTION DIODE; TOTAL-ENERGY CALCULATIONS; SNO2 THIN-FILMS; OPTICAL-PROPERTIES; SPATIAL EVOLUTION; AL-SC; TRANSPARENT; GROWTH; ABSORPTION; FLUORINE